Rhizobial inoculation influences seedling vigor and yield of rice - Biswas, Jatish C.; Ladha, Jagdish K.; Dazzo, Frank B.; Yanni, Youssef G.; Rolfe, Barry G. (Wiley, 2000)
Rice (Oryza sativa L.) is one of the world's most important crops. The present investigation was designed to assess the range of growth‐promoting activities of various diazotrophic bacteria on rice seedling vigor, its carryover effect on straw and grain yield, and the persistence of an inoculant strain on rice roots under greenhouse conditions. Growth responses to inoculation exhibited bacterial strain–rice variety specificity that were either stimulatory or inhibitory. Growth responses included changes in rates of seedling emergence, radical elongation, height and dry matter, plumule length, cumulative leaf and root areas, and grain and straw yields. Most notable were the inoculation responses to Rhizobium leguminosarum bv. trifolii E11 and Rhizobium sp. IRBG74, which stimulated early rice growth resulting in a carryover effect of significantly increased grain and straw yields at maturity, even though their culturable populations on roots diminished to below detectable values at 60 d after planting. The test strains were positive for indole‐3‐acetic acid production in vitro, but only some reduced acetylene to ethylene in association with rice under laboratory growth conditions. These studies indicate that certain strains of nonphotosynthetic diazotrophs, including rhizobia, can promote growth and vigor of rice seedlings, and this benefit of early seedling development can carryover to significantly increased grain yield at maturity.